2016
DOI: 10.1007/s13127-016-0289-z
|View full text |Cite
|
Sign up to set email alerts
|

Does size matter for horny beetles? A geometric morphometric analysis of interspecific and intersexual size and shape variation in Colophon haughtoni Barnard, 1929, and C. kawaii Mizukami, 1997 (Coleoptera: Lucanidae)

Abstract: Colophon is an understudied, rare and endangered stag beetle genus with all species endemic to isolated mountain peaks in South Africa's Western Cape. Geometric morphometrics was used to analyse intersexual and interspecific variation of size and shape in the mandibles, heads, pronota and elytra of two sympatric species: Colophon haughtoni and Colophon kawaii. All measured structures showed significant sexual dimorphism, which may result from male-male competition for females. Female mandibles were too small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Males of C. kawaii were significantly larger than C. haughtoni for all structures. Their results support the species status of C. kawaii , which was in doubt due to its hybridization with C. haughtoni (Eldred et al 2016). In another study, Tabatabaei Yazdi and Adriaens (2013) utilized skull shape and size in geometric morphometric analysis to identify four rodent species ( Meriones tristrami Thomas, 1892, Meriones persicus (Blanford, 1875), Meriones vinogradovi Heptner, 1931, and Meriones libycus Lichtenstein, 1823).…”
Section: Discussionsupporting
confidence: 59%
“…Males of C. kawaii were significantly larger than C. haughtoni for all structures. Their results support the species status of C. kawaii , which was in doubt due to its hybridization with C. haughtoni (Eldred et al 2016). In another study, Tabatabaei Yazdi and Adriaens (2013) utilized skull shape and size in geometric morphometric analysis to identify four rodent species ( Meriones tristrami Thomas, 1892, Meriones persicus (Blanford, 1875), Meriones vinogradovi Heptner, 1931, and Meriones libycus Lichtenstein, 1823).…”
Section: Discussionsupporting
confidence: 59%
“…Similar results were obtained in the present study, where the differences concern mainly vein Rs as well as the distances between landmark 7 to fore and hind margin, and between landmarks 11 to 6 and 1. Geometric morphometrics has also been used to discriminate species in other insect orders, including Hemiptera (Aghagoli et al ., 2013), Hymenoptera (Mitrovski-Bogdanović et al ., 2014), and Coleoptera (Zúñiga-Reinoso and Benítez, 2015; Eldred et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although there many studies have found significant differences in pronotum shape in Coleoptera (Pizzo et al, 2006;Ober & Connolly, 2015;Eldred et al, 2016;Li et al, 2016), geometric morphometrics was applied here to Dorcadion for the first time. Combining pronotal shape morphology with phylogenetic analysis Ober & Connolly (2015) showed that the pronotum shape generally reflects phylogenetic relationships, and may be the most important morphological trait for recognizing distinct populations of Scaphinotus petersi Roeschke, 1907 (Coleoptera: Carabidae) in the Arizona Sky Islands.…”
Section: Resultsmentioning
confidence: 99%